Crafting development power: Evolving European approaches in an age of polycrisis - Yunnan Chen; Raphaëlle Faure; Nilima Gulrajani (Overseas Development Institute (ODI), 2023)
Amid the polycrises of Covid-19, the conflict in Ukraine and the intensification of geopolitical tensions, mid-size European donors face pressures to leverage development cooperation to secure their foreign policy goals. These donors now deploy a diverse toolbox of development levers to cultivate influence and achieve strategic goals, including concessional aid, economic cooperation, engagement with the multilateral system and investing in global public goods. While donors recognise the importance of volumes of development finance in crafting their status as a 'development power', other non-financial elements including technical capacity, institutional autonomy and commitment to national values also form a source of influence with peers and partners in the Global South. Among the countries examined (France, Germany, Sweden and the UK), this paper identifies four emergent strategies for cultivating development power based on the degree to which their efforts are targeted and active.
Keywords: 330; France; Aid; Germany; Sweden; Development finance; United Kingdom (UK)